2015
DOI: 10.1371/journal.pone.0126161
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Motifs of Watermelon Silver Mottle Virus NSs Protein Are Responsible for RNA Silencing Suppression and Pathogenicity

Abstract: The NSs protein of Watermelon silver mottle virus (WSMoV) is the RNA silencing suppressor and pathogenicity determinant. In this study, serial deletion and point-mutation mutagenesis of conserved regions (CR) of NSs protein were performed, and the silencing suppression function was analyzed through agroinfiltration in Nicotiana benthamiana plants. We found two amino acid (aa) residues, H113 and Y398, are novel functional residues for RNA silencing suppression. Our further analyses demonstrated that H113 at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 57 publications
1
16
0
1
Order By: Relevance
“…The aromatic residues W, F, and Y are known to be important for protein stability and function. For example, the aromatic ring of Y 398 in the WSMoV NSs protein has been shown to affect NSs stability and its RNA silencing suppression activity (Huang et al, 2015). Deletion of five residues, including an aromatic residue, from the readthrough protein of potato leafroll virus affects viral systemic infection and disease symptom induction (Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The aromatic residues W, F, and Y are known to be important for protein stability and function. For example, the aromatic ring of Y 398 in the WSMoV NSs protein has been shown to affect NSs stability and its RNA silencing suppression activity (Huang et al, 2015). Deletion of five residues, including an aromatic residue, from the readthrough protein of potato leafroll virus affects viral systemic infection and disease symptom induction (Xu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In case of Watermelon silver mottle virus (WSMV), Huang et al [20] showed that mutations at H 113 in the common epitope (CE) ( 109 KFTMHNQ 117 ) and Y 398 at the C-terminal β-sheet motif ( 397 IYFL 400 ) affect NSs mRNA stability, and protein stability, respectively, and concluded that both are critical for silencing suppressor activity of NSs. The H 113 of WSMV corresponds to H 115 in TSWV sequence and is also conserved in all species of the genus.…”
Section: Discussionmentioning
confidence: 99%
“…The crosstalk of RNA silencing and SA signaling was also demonstrated [ 59 ]. Since the RSS NSs of a tospovirus can restore a non-local lesion HC-Pro mutant of ZYMV [ 61 ], it is inferred that the GCFSV NSs might also be involved in HR formation on C . quinoa plants.…”
Section: Discussionmentioning
confidence: 99%